Profil penyelesaian soal SPLDV berdasarkan teori apos ditinjau dari kemampuan matematika siswa - Yunita, Rezki Lola; Pathuddin, Pathuddin; Alfisyahra, Alfisyahra; Lefrida , Rita (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2024)
This research was conducted to obtain descriptions of students in solving systems of two-variable linear equations (SPLDV) based on APOS theory in terms of mathematical ability. This type of research is descriptive with a qualitative approach. The subjects in this research were 3 students in class VIII B of SMPN 20 Palu in the odd semester 2023/2024 consisting of 1 student with high mathematics ability, 1 student with moderate mathematics ability, and 1 student with low mathematics ability. Data in the research were collected through written tests and interviews with subjects. The research results show that: (1) Students with high mathematical abilities can solve SPLDV questions by achieving all stages of APOS theory (action, process, object, and scheme); (2) Students with moderate mathematical abilities can solve SPLDV questions but have not been able to reach all stages of APOS theory, students with moderate mathematical abilities are only able to reach the APO stage (action, process and object); (3) Students with low mathematical abilities have not been able to solve SPLDV questions and are only able to reach the action stage at the APOS theory stage.